UJI BEBERAPA ISOLAT Trichoderma sp UNTUK MENGEP«)ALIKAN PENYAKITBUSUKmTAMPADATANAMANANGGREK DENDROBIUM - Yunel Venita; Muhammad Ali; Rahmadia ' (Universitas Riau, 2010)
Objective of this research was to test the ability of Trickottermasp isolate andget the best isolate incontrolling blighted leave disease on dendrobium orchid. TUs research was conducted cxperimentelly usingCompletely Randondzed Design (RAL) byfivetreatments of TridHHlerma sp isoUte (TO « without TrichuJennmsp,TI 'isotateT-ag,T2-=T-«a,T3>T-k,T4'^b). Resultof research indicates that application of some isolateon dendrobium orchid gives different influence hi controlling blighted leave disease on orchid. In controllingPhytopktkon sp.. Isolate T-ag is better because it has stronger hihibition ability.